Expressão de anexina II em oócitos e no desenvolvimento embrionário bovino - Costa, Luís Fabiano Santos da (2004)
The present study as conducted to examine semiquantitative gene expression of annexin II (ANEII) during all follicular phases of folliculogenesis in bovine, in preantral follicles and oocytes of antral follicles too in different size (<3mm, 5-8mm e >9mm in diameter). It was investigated the gene expression of ANEII influenced by retinol during oocyte maturation. In addition we examine annexin II (ANEII) presence during embryonic development and regulation of gene expression to ANEII by retinol and insulin like growth factor (IGF-I) was availed. Bovine ovaries from adults and fetal females was collected in abattoir and cumulus-oocyte complexes and preantral follicles were recovered. mRNA extraction and cDNA formation was carried out to produce ANEII amplification by polymerase chain reaction. Bovine embryos were used at initial phases of development from in vitro production in SOF medium or retinol and/or IGF-I supplemented. Bovine embryos were submitted to mRNA extraction and cDNA formation and ANEII amplification was obtained by polymerase chain reaction (PCR). Preantral follicles at secondary stages presented gene expression to ANEII. Oocytes from different follicular sources in germinal vesicle (GV) stage were significantly different (p<0,05) in gene expression. Gene expression to ANEII in oocytes of larger 8mm follicles were significantly higher than those from 3mm and 5-8mm (p<0,05). The similar results were obtained in metaphase II (MII) phase. However difference was not observed between oocytes from 3mm and 5-8mm follicles. Oocytes from follicles larger 8mm presented higher ANEII expression than those from 3mm follicles, but difference was not observed to the oocytes from 5-8mm (p<0,05). The ANEII gene expression was increase with retinol supplementation during maturation process in contrast to control group (p<0,05). The ANEII was present during early embryonic development except in 16 cells. The rate of embryo production was increased by supplementation with retinol in culture medium (p<0,05) in contrast with control and IGF-I group. The control group (20,5%; 24/117) was similar with IGF-I group (25,8%; 24/93) and both were significantly lower than retinol (37,8%; 45/119). Semi quantitative analyses of ANEII gene expression was significantly higher in control group than retinol or IGF-I embryo treated (p<0,05). However retinol and IGF-I were not different. ANEII have more expression in oocytes in capacitating process. Retinol increases the mRNA availability to ANEII and could be involved in oocyte competence. In conclusion, in vitro embryo production is increased by retinol supplementation and could be regulating the gene expression of ANEII during embryo development. Decrease in gene expression to ANEII determines a qualitative and quantitative increase in in vitro embryo production.